Between minilateralism and multilateralism: opportunities and risks of pioneer alliances in international trade and climate politics - Clara Brandi; Axel Berger; Dominique Bruhn (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
Global challenges such as climate change or the dismantling of protectionism can only be countered through enhanced forms of global co-operation. Traditional multilateral co-operation has come up against limits in recent years. For example, efforts to achieve an international climate treaty have taken many years, with this now set to be signed at the end of 2015 in the scope of the United Nations Framework Convention on Climate Change (UNFCCC). At the World Trade Organization (WTO) the negotiation of the Doha Development Agenda has been extremely slow for many years. To lend new impetus to international trade and climate politics it is necessary to discuss innovative forms of co-operation, such as in the form of minilateral or plurilateral initiatives, in other words sub-groups of multilateral actors. In the global trading system many countries have reacted to the stuttering progress of the multilateral process by concluding bilateral and regional treaties outside of the WTO. In particular, the negotiation of ever-larger mega-regional treaties such as the Transatlantic Trade and Investment Partnership (TTIP) and the Transpacific Partnership (TPP) mark a turning point in the global trade system. The content of these treaties frequently extends beyond agreements in the multilateral context. Minilateral alliances in international trade politics are frequently viewed critically. They are regarded as second-best options – or no good solution at all – compared to multilateral agreements, as they may lead to detrimental effects on countries that are not part of the negotiations, as well as tying-up capacity and reducing incentives for the conclusion of the Doha Round. To the extent that demand exists for minilateral negotiations, these should therefore take place in the scope of the WTO. This requires the reaching of a compromise in the WTO that enables more efficient negotiations whilst at the same time supporting an inclusive, multilateral trading system. Consequently, it should be discussed whether and under which conditions plurilateral treaties should be accorded more scope within the WTO. Pioneer alliances offer great potential for international climate policy, particularly where they also include sub-national and non-governmental actors. However, the same applies for climate politics as with trade politics: minilateral pioneer alliances should augment the multilateral process, not replace it, even supporting it in the ideal scenario. Although numerous international climate initiatives have already been formed, they tend to generate merely marginal rather than transformative changes. The basis for a transformative pioneer alliance could be, for example, the Renewables Club formed by Germany in 2013 along with nine other countries. In order for this club to become a transformative pioneer alliance it needs to first fulfil a number of key conditions: the members need to agree on a joint, ambitious vision and corresponding objectives; they need to concur on how to create additional benefits for all members; and they should support transformative strategies for climate protection and climate resilience in other parts of the world. In addition, it should also be ensured that minilateral alliances do not undermine multilateral forums, but instead complement them. After the COP21 it is necessary to discuss how pioneer alliances can be utilised to support ambitious climate policies and also the effective implementation of the agreements reached in Paris, e.g. by strengthening the ratchet-up mechanism.
Keywords: 330; Klimawandel; Handel und Investitionen; Regionale + globale + transnationale Governance